2017
DOI: 10.1002/jcp.26184
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of P2Y12 in the superior cervical ganglia alleviates abnormal sympathetic activity after myocardial ischemia

Abstract: Superior cervical ganglia (SCG) innervate the myocardium and participate in sympathoexcitatory transmission. P2Y receptor is expressed in satellite glial cells (SGCs). This study seeks to clarify whether the P2Y receptor is involved in the sympathoexcitation reflex after myocardial ischemia (MI). MI model was induced by occlusion of the left coronary artery. P2Y were assayed by real time PCR and Western blotting. Our results showed that expression levels of P2Y mRNA and protein were significantly higher in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…It is also expressed in SGCs of SG [27]. Upregulation P2Y 12 receptor in the SGCs of superior cervical ganglia participates in the sympatho-excitatory reflex after myocardial ischemia [23]. Second, overexpression of P2Y 12 receptor in SG increased blood pressure, heart rate and cervical SND in non-diabetic rats whereas treatment of P2Y 12 shRNA could decrease the elevated blood pressure, heart rate and cervical SND occurring in diabetic rats.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It is also expressed in SGCs of SG [27]. Upregulation P2Y 12 receptor in the SGCs of superior cervical ganglia participates in the sympatho-excitatory reflex after myocardial ischemia [23]. Second, overexpression of P2Y 12 receptor in SG increased blood pressure, heart rate and cervical SND in non-diabetic rats whereas treatment of P2Y 12 shRNA could decrease the elevated blood pressure, heart rate and cervical SND occurring in diabetic rats.…”
Section: Discussionmentioning
confidence: 97%
“…The autonomic ganglia include sympathetic and parasympathetic ones. The cervical sympathetic nervous system contributes to the maintenance of cardiovascular homeostasis [23]. Cardiac sympathetic innervation is largely made by the superior cervical ganglia (SCG) and the stellate ganglia (SG) [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Purinergic signaling has pivotal roles in physiological and pathophysiological cardiovascular processes ( Vassort, 2001 ; Erlinge and Burnstock, 2008 ; Kennedy et al, 2013 ; Burnstock and Pelleg, 2015 ). Purinergic P2Y receptors have been implicated in the treatment of cardiovascular diseases ( Nishimura et al, 2017 ; Zou et al, 2017 ). In the present study, we demonstrated that both the expression levels of P2Y 12 receptor mRNA and protein in DRG of MI rats were increased.…”
Section: Discussionmentioning
confidence: 99%
“…P2Y 12 receptors are expressed in SGCs of DRG ( Kobayashi et al, 2008 ; Katagiri et al, 2012 ). Additionally, P2Y 12 receptors expressed in SCG are involved in mediating the sympathoexcitatory reflex ( Zou et al, 2017 ). DRGs have primary sensory neurons, however, the role of the P2Y 12 receptor in DRG SGCs during MI remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%